Tool to assess the groundstroke technique of preadolescent tennis players - Diler, Hakan; Şahan, Asuman; Erman, Kemal Alparslan (Frontiers in Sports and Active Living, 2024)
Objective In this study, we develop a tool that can be used by tennis coaches to evaluate the groundstroke (forehand and backhand) technique of preadolescent tennis players. Methods The participants of the study were 60 children (30 males and 30 females) aged 10–12 years, with at least two years of training in tennis. The Groundstroke Correction Checklist (GCC) was translated into Turkish by using a blind procedure. The Turkish translation was then evaluated by 15 coaches of the Turkish Tennis Federation who had at least a level-3 coaching license and more than five years of coaching experience. The technical components related to technique in the checklist were labeled as unimportant, important, and very important. Following this, the GCC was converted into a Groundstroke Technique Assessment Test Tool (GTATT) by a selection committee consisting of three experts, and its reliability and validity were assessed by using it in the field. Spearman's correlation was used to analyze the correlation (test-r test) between the technical evaluation scores assigned to the players by the tennis coaches based on the GTATT in the first and second weeks. Intra- and inter-rater reliability was used to analyze the overall scores of technical evaluations in the first and second weeks to assess the reliability of the scale used. We determined each player's number of years of playing experience (TPY), technical evaluation (TE), international tennis-level test score (ITN), I-cord classification order (ICCO), and the number of games won (GW) in a tournament organized among themselves and evaluated the correlations among these parameters by using Spearman's correlation analysis. Conclusion A statistically high and significant correlation was observed between the technical evaluations of the players' forehand and backhand groundstrokes by the tennis coaches by using the GTATT in the first and second weeks (r > .90, p < .01). The analysis of the intra- and inter-rater reliability of the GTATT yielded excellent agreement between the technical observations of the three coaches of the players' forehand and backhand strokes in the first and second weeks.